Efficacy of magnetic resonance imaging in the diagnosis of perianal hidradenitis suppurativa, complicated by anal fistulae: A report of two cases and review of the literature - Takiyama, Hirotoshi (Int J Surg Case Rep, 2015)
BACKGROUND: Perianal hidradenitis suppurativa (PHS) is a chronic recurrent inflammatory disease of the apocrine glands present in the skin and soft tissue adjacent to the anus. It is often misdiagnosed or treatment is delayed, resulting in the formation of an abscess or, in the worst case, leading to sepsis. It is difficult to treat perianal lesions merged with fistulae completely due to its high recurrence rate. Therefore, we should diagnose it correctly and treat it with appropriate methods. PRESENTATION OF CASE: We report two cases of PHS with anal fistulae that were examined preoperatively using magnetic resonance imaging (MRI) and treated safely by surgery without any recurrence. DISCUSSION: The anal sphincter area cannot be visualized and evaluated directly by fistulography. Also CT has only limited resolution, making it difficult to distinguish between soft tissues and inflammatory streaks. Endosonography is not suitable for the examination of supra-sphincteric or extra-sphincteric extensions, as it is limited by insufficient penetration of the ultrasonic beams. MRI can demonstrate the entire course of the fistulae owing to its high contrast resolution. CONCLUSION: Our findings support the idea that PHS with complicated anal fistulae can be diagnosed accurately using MRI and treated safely and completely with surgery.